Factors Cause of Switching Shorter Regimen to Longer Regimen in Multidrug-Resistant/ Rifampicin-Resistant Tuberculosis Treated Patients in Dr. Soetomo Hospital Surabaya, Indonesia - Soedarsono Soedarsono1,2, Tutik Kusmiati1,2, Prastuti Asta Wulaningrum1 , Ariani Permatasari1 , Dwi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Indonesia started to implement the Shorter Regimen (STR) since 2017, but not all of MDR/RR-TB patients were treated with STR until the end of treatment. The presence of side effects of one orseveral drugs in the STR and the resistance to fluoroquinolone and or 2nd line injection drug after startingtreatment caused a switch in regimen from STR to a longer regimen. This study was conducted to evaluatethe factors that caused switch STR to the longer regimen.Methods: This was a descriptive study in MDR/RR-TB patients who received STR from October 2017to December 2019. Patients who switch their regimen were analyzed and determine the factors cause ofswitching STR to a longer regimen.Conclusion: The major cause of switching was due to the presence of resistance to fluoroquinolone and 2ndline injection drugs and incidence of prolonged QT. A diagnostic rapid test such as the line probe assay 2ndline TB drugs is absolutely a screening tool to determine MDR-TB patients, pre-XDR-TB or XDR TB assoon as the regimen is given. Monitoring and efforts to overcome prolonged QT side effects are also neededto prevent switch regimens that can affect the patient’s psychological condition.